Why are patients not more involved in their own safety? A questionnaire-based survey in a multi-ethnic North London hospital population. Issue 1123 (25th May 2019) - Yoong, Wai; Assassi, Zouina; Ahmedani, Iman; Abdinasir, Rahma; Denning, Max; Taylor, Harriet; Chandrakumar, Danya; Kwakye, Michael; Nauta, Maud
Abstract: Purpose: Active patient participation in safety pathways has demonstrated benefits in reducing preventable errors, especially in relation to hand hygiene and surgical site marking. The authors sought to examine patient participation in a range of safety-related behaviours as well as factors that influence this, such as gender, education, age and language. Design: A 20-point questionnaire was employed in a London teaching hospital to explore safety-related behaviours, particularly assessing patient's willingness to challenge healthcare professionals and engagement in taking an active role in their own care while in hospital. Data was also collected on participant demographic details including gender, age, ethnicity, English language proficiency and education status. Results: 85% of the 175 patients surveyed would consider bringing a list of their medications to hospital, but only 60% would bring a list of previous surgeries. Only 45% would actively engage in the WHO Safer Surgery Checklist and over three quarters (80%) would not challenge doctors and nurses regarding hand hygiene, believing that they would cause offence. Female patients who had tertiary education, were fluent in English and less than 60 years of age were statistically more likely to feel responsible for their own safety and take an active role in safety-related behaviour while in hospital (p<0.05). Conclusions: Many patients are not engaged in safety-related behaviour and do not challenge healthcare professionals on safety issues. Older male patients who were not tertiary educated or fluent in English need to be empowered to take an active role in such behaviour. Further research is required to investigate how to achieve this.